Fire resistance of high-strength self-compacting concrete - Abdul Rahman Abdul Aziz (Nanyang Technological University, 2021)
As the demand for underground infrastructure increases with the increasing population in urban cities, the construction of long spans and large capacity designs of underground concrete structures is crucial in providing adequate space for future expanding services. The use of self-compacting concrete (SCC) is a great solution as a construction material for the development of these structures through its effective and sustainable design. Advantages including high flowability, high workability, high deformability results in an easier and faster construction process, while its low permeability and good segregation resistance results in better durability. However, the current drawback of using SCC involving its limited compressive strength (less than 80MPa) and explosive fire spalling behaviour, limits is use in the building sector today. In this project, the focus was on improving SCC to achieve high-strength, fire resistance while maintaining its self-compactability and high workability. A three-stage process was taken to achieve this. First, the objective was to achieve high strength by investigating the effect of supplementary cementitious materials (SCMs) such as fly ash and silica fume on the fresh and hardened properties of SCC. The next stage was to investigate the effects of fibres such as polypropylene (PP) and steel, on the fresh, hardened, and residual properties of SCC. The last stage was to investigate the fire resistance of fibre-reinforced high-strength SCC. The current study first proposes that an optimised mix design of 30% fly ash and 10 % silica fume in replacement of cement can achieve excellent workability and at the same time, the presence of a small amount of silica fume provides an early strength development and fly ash provides a long term strength development. Furthermore, the use of PP fibres makes the concrete rather clingy resulting in increasing of the adhesion and cohesiveness. Hence, it causes in a lower rate of bleeding and segregation but a reduced slump and flowability compared to the normal SCC. Furthermore, the addition of polypropylene (PP) fibres decreases the compressive strength of SCC while addition of steel fibres improves both the tensile and compressive strength of SCC as it improves ductility and prevents propagation of cracks. In regard to the fire performance of SCC, the addition of PP fibres can prevent fire spalling, as the melting of PP fibres creates channels for pore pressure to escape. However, the increase in permeability results in a decrease in compressive strength of SCC. Finally, the deployment of hybrid fibres in high-strength SCC can achieve good flowability and workability and exhibits great improvement in the compressive strength of SCC. The hybrid-fibre reinforced high-strength selfcompacting concrete (HFRHSSCC) is able to prevent explosive spalling and shows excellent mechanical properties when exposed to high temperatures up to 400℃, but there is not a definite conclusion on its effectiveness in improving residual properties when the temperature exceeds 400℃ compared to normal fibre-reinforced SCC.